Academic and professional master’s students before pandemic: The past helping the present and projecting the future - Junior , Gilmar Jorge de Oliveira; Gonçalves , Marcos José; Silva, Odilon Novaes (Seven Editora, 2024)
Use information about the profile, lifestyle, and health of master’s students before the COVID-19 pandemic, to assist in institutional and personal decision-making, both health and educational, for the present moment and future. The aim of this study was to identify and compare the sociodemographic, academic, and health characteristics of academic and professional master’s students before the pandemic. The sample consisted of 375 master’s students from a public university in the Brazilian Midwest, 306 academics and 69 professionals, who answered the instruments (Epworth Sleepiness Scale and SRQ-20), in addition to questions developed by the researchers. Academic and professional master’s students showed significant differences in the variables age, religion, and alcohol consumption. Regarding academic characteristics, both highlighted their advisors. However, the results obtained before the pandemic already showed an unsatisfactory scenario, indicating the need to implement actions that would promote improvements in the mental health of students, regardless of the type of master’s degree. DOI:https://doi.org/10.56238/sevened2024.007-004